Additional file 1 of CAFs-derived SCUBE1 promotes malignancy and stemness through the Shh/Gli1 pathway in hepatocellular carcinoma - Jungang Zhao; Rizhao Li; Jiacheng Li; Ziyan Chen; Zixia Lin; Baofu Zhang; Liming Deng; Gang Chen; Yi Wang (figshare, 2022)
Supplementary Material 1
Keywords: Medicine; Molecular Biology; Chemical Sciences not elsewhere classified; Biological Sciences not elsewhere classified; Cancer; Science Policy